Verkorting van die Ae. peregrina-verhaalde Lr59-translokasie van koring - Kotze, Luigia (2009)
The aim of this study was to analyse testcross-material that was generated during a homoeologous pairing-induction experiment. Absence of the homoeologous pairing suppressor gene, Ph1, was employed to induce meiotic pairing between the Lr59 translocation (Aegilops peregrina) and 1AL of normal wheat. The study aimed to characterize the test-cross plants derived from this experiment and to identify recombinants which retained the least amount of species chromatin but which still contained the Lr59 gene. The test-cross F1 population, 07M5 (total 635 plants), was screened for Lr59 resistance by inoculating seedlings with the leaf rust pathotype, UVPrt8. The 168 resistant plants were characterized with molecular markers in order to identify recombinants. The data were used to construct a physical map which showed the relative sizes of the recombinants and which could be used to identify those recombinants which contained the least amount of residual species chromatin. Microsatellite (Xcfa2219, Xbarc83 and Xgwm164) and SCAR (S15T3) analysis was used for the initial identification of recombinants. The results showed that 152 of the 168 resistant plants were recombinants for the four loci; that eight of the remaining 16 plants represented non-recombinant, wild species-types and that the last eight plants represented the wheat parental-types which were resistant (and thus, also recombinants). This extremely high recombination frequency can largely be attributed to strong segregation distortion that was evident in the cross. It is also possible that the translocation segment could derive from the S genome rather than the U genome of Ae. peregrina. The S genome is closer related to the wheat genomes than the U genome and may be more prone to recombination. With the use of the microsatellite and SCAR data, a physical map was constructed which showed the relative location of the Lr59 gene on the translocation. It appeared that the eight shortest recombinants retained terminal species chromatin. In an attempt to characterize the eight recombinants, additional marker loci had to be identified within that region. RAPD, iv AFLP and DArT markers were investigated for this purpose. RAPD analyses did not produce any useful markers. AFLP and DArT analyses did identify useful markers with which the eight recombinants could be screened. The data showed which recombinants probably retained the least amount of species chromatin. Seeing that AFLP and DArT markers are anonymous and that the distances between marker loci are unknown, it is not possible to say which recombinant is the shortest and consequently it will be nessecary to also evaluate the group of eight recombinants agronomically in order to identify the most useful ones. The results showed that multiple cross-overs apparently occured on both sides of Lr59. Multiple cross-overs are higly unlikely in material of this nature, therefore it was speculated that the observation resulted from incomplete synteny between the telomeric areas of the translocation and 1AL. A structural difference between the two chromosome regions might have given rise to abnormal meiotic pairing structures and thus unexpected gamete genotypes. Each of the eight recombinants did express one or more of the Ae. peregrina derived AFLP loci which can in future be verified for use as a marker for marker assisted selection. The study succeeded in identifying a number of potentially useful recombinants which contain the Lr59 resistance. It would, however, be risky to select only one of the shortest recombinants for further development on the basis of the present knowledge as some recombinants may contain genetic abnormalities which resulted from reduced synteny in the Lr59 region. It would therefore be wise to further evaluate all eight recombinants before the best one is selected for agronomic use.